Application of safety triad in preparation for climate extremes affecting the process industries. Issue 3 (31st July 2019) - Parker, Trent; Shen, Ruiqing; O'Connor, Michael; Wang, Qingsheng
Abstract: A number of incidents within the process industries have been attributed to climate extremes. The late Dr. Mannan proposed the concept of a "safety triad, " which represents the three layers of an effective safety system, with deficiencies in any of the layers leading to possible incidents. Using this safety triad, past incidents in the process industries resulting from climate extremes can be investigated. From these investigations, appropriate systems and strategies can be implemented to address deficiencies in any of the layers to reduce the likelihood of similar incidents occurring in the future. This article presents a case study involving the DuPont La Porte facility toxic chemical release to demonstrate the use of the safety triad to identify deficiencies of the layers that led to the incident and propose strategies to address them.